Simplified numerical model for high-strength bolted connections. (1st June 2018) - Zhao, Zhongwei; Liang, Bing; Liu, Haiqing; Li, Yongjing
Highlights: A simplified establishing method of high-strength bolted connection was proposed. The method to determine real constant of friction element was proposed. Sliding phenomenon can be exactly captured by simplified numerical models. The simplified model can be exactly adopted in quasi-static analysis. Abstract: Numerical method has become one of the main methods for investigating the mechanical behavior of high-strength bolts. However, its high computation cost and non-convergence make its application in joints containing refined bolted models impossible. A new bolt-slip model was proposed for the simulation of high-strength bolted connection based on this background. The method to determine the real constant of the friction element was also proposed. The results derived by the newly proposed bolt-slip model were compared with the results derived by the existing numerical model and experimental work. The comparison results indicated that the sliding phenomenon can be well captured and the friction force with enough accuracy can be derived by the proposed bolt-slip model. Results indicate that the proposed bolt-slip model can significantly reduce computation time with high accuracy kept.